Efeitos do CPTPP sobre os principais setores econômicos e sobre o bem-estar econômico das famílias nas macrorregiões brasileiras - Gelatti, Elisangela (2020)
This aimed to measure the economic and distributive impacts that the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) may have on the main economic sectors and on the economic of families in Brazilian macroregions, under an alternative hypothesis regarding possible integration of Brazil into such an agreement. For this, we used a multi-regional, multisectoral Computable General Equilibrium Economic Model for the Brazilian Economy (PAEG) with ten income classes for the Brazilian macroregions. The economic results show that Brazil's adherence to the CPTPP stimulates welfare, GDP, and the production of Brazilian exports, especially agribusiness. Non-participation, on the other hand, has detrimental effects on the Brazilian economy, damaging both GDP and the well-being of Brazilian macro-regions. On the other hand, with Brazil's adherence to CPTPP, the results are beneficial for all income classes of Brazilian families, since all classes presented welfare gains. With the exception of the Southeast, whose region in which there would be an increase in the welfare gap between the poorest and the richest families, Brazil's adherence to CPTPP converges towards a decrease in welfare inequality of the families of the Brazilian macroregions. In general, the results show that the formation of a free trade area between the CPTPP countries and Brazil tends to intensify their trade, as well as to make the factors of capital and labor production more efficient. In addition to causing a decrease in the inequality of welfare of Brazilian families in each macroregions, making the distributive effects of trade more harmonious.